2009
DOI: 10.1007/s12204-009-0620-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear aerothermoelastic modeling and behavior of a double-wedge lifting surface

Abstract: The design of the re-entry space vehicles and high-speed aircraft structures requires special attention to the non-linear thermoelastic and aerodynamic instabilities. The thermal effects are important since temperature environment influences significantly the static and dynamic behaviors of flight structures in supersonic/hypersonic regimes. The dynamic behavior of a double-wedge lifting surface with combined freeplay and cubic stiffening structural nonlinearities in both plunging and pitching degrees-of-freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The initial conditions had the effect of creating a chaotic response. The results presented here add to the work done where chaotic motion and limit cycle oscillations were predicted for a two-dimensional aerofoil with stiffness nonlinearities [15,33,38,50] or aerodynamic nonlinearities [2].…”
Section: Fig 24supporting
confidence: 60%
See 1 more Smart Citation
“…The initial conditions had the effect of creating a chaotic response. The results presented here add to the work done where chaotic motion and limit cycle oscillations were predicted for a two-dimensional aerofoil with stiffness nonlinearities [15,33,38,50] or aerodynamic nonlinearities [2].…”
Section: Fig 24supporting
confidence: 60%
“…Lee and Tron [21] showed that loose control surfaces can be adequately represented via either a bilinear spring stiffness or a cubic nonlinearity, by modelling the LCOs seen in the CF-18 aircraft. A considerable amount of research has gone into investigating the aeroelastic response of an aerofoil with bilinear nonlinearities in either the plunge or pitch degrees of freedom [2,22,29,32,33,36], with limited research on three-dimensional aeroelastic models for high-speed application [3,4,23,30]. Free-play nonlinearities usually occur in the control surface [16], whereas the cubic stiffness comes mainly from the large amplitude oscillation of the flexible wing [19].…”
Section: Introductionmentioning
confidence: 99%